ANALISIS PENGENDALIAN KUALITAS PRODUK DENGAN MENGGUNAKAN STATISTICAL QUALITY CONTROL (SQC) (STUDI KASUS: PADA PT. ANUGERAH INDOFOOD BAROKAH MAKMUR) - Altatit Dianawati; Rizal Akbar (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
PT. Anugerah Indofood Barokah Makmur is a company engaged in the processing of packaged drinks. This type of research was conducted using descriptive data analysis methods. The research method used is data collection by means of observation and interviews, population damage data during the production process, damage data findings from the results of the inspection process and damage data found by consumers, sampling for the product inspection process, namely 1% of the total production per shift. , followed by processing the data using the SQC method, steps were carried out including filling out the examination sheet, making histograms, making pareto diagrams, calculating control charts and making causal diagrams.The results showed that there were three types of damage to Ichi Ocha and Fruitamin Cocobit products, namely damage to the position cap, damage to the No coding cap, and damage to the position label. The results of the analysis of the causeand-effect diagram showed the causes of poor quality Ichi Ocha and Fruitamin Cocobit products, namely labor factors, methods, and machines. It can be seen from the Pareto diagram, the type of product damage is more dominant in the Cap position size of 62.61%, the results of the control chart analysis show that quality control at PT. AIBM is still out of control. Actions taken to reduce damage include adding labor to the inspector section of the packing area, often verifying the camera machine heuft / inspection, carrying out maintenance on the engine and the stock on spare parts is still not controlled.